2022
DOI: 10.3390/ijerph192013514
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Review of Environmental Audit Tools for Public Open Spaces from the Perspective of Children’s Activity

Abstract: Public open spaces are important venues for children’s participation in outdoor activities and social life. This study performs a comparative and qualitative review of the tools that can be used to audit the environments of children-focused public open spaces. The analysis reviews 25 studies involving 11 tools for comparison. The results reveal that (1) the tools were developed in different fields; (2) the tools use two data resources, field investigation and geographic databases; (3) the tool dimensions are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…After reviewing 25 studies across 11 sources, Chinese scholar Xue Meng identified several factors that influence child-friendly pocket parks. These factors can be broadly classified as follows: the environment and its accessibility, the perceived level of safety and opportunities for physical activity and recreation, and the visual attractiveness and comfort of the surrounding area [17].…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing 25 studies across 11 sources, Chinese scholar Xue Meng identified several factors that influence child-friendly pocket parks. These factors can be broadly classified as follows: the environment and its accessibility, the perceived level of safety and opportunities for physical activity and recreation, and the visual attractiveness and comfort of the surrounding area [17].…”
Section: Introductionmentioning
confidence: 99%